Kingdom of Lesotho : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on the Kingdom of Lesotho reviews the broad objectives and key institutional features of the Common Monetary Area (CMA) relating to currency arrangements. The CMA Agreement provides for the three small member countries to have access to South African capital and money markets, but only through prescribed investments or approved securities that can be held by financial institutions in South Africa. Lesotho's exchange rate arrangement under the CMA shares certain characteristics of a currency board.